Preparation and Characterization of (PMMA-Berry Paper or Plan Leaves) Composites - Farhan Lafta Rashid; Ahmed Hashim; Fadhil Saeed Hasan; Saba R. Salman; Hind Ahmed (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2013)
In this paper, study the effect of addition the Berry Paper or Plan Leaves on optical properties of PMMA. The samples have been prepared by casting technique and different thickness. . The absorption and transmission spectra have been recorded in the wavelength range (200 – 800) nm. The experimental results show that the absorption coefficient, energy gap of the indirect allowed and forbidden  transition, extinction coefficient, read and imaginary dielectric constant and refractive index are changing with increase the of Berry Paper or Plan Leaves concentration.